ChemInform Abstract: Cyclic Tungstoselenites Based on Se2W12 Units. Issue 17 (28th April 2014) - Kalinina, Irina V.; Peresypkina, Eugenia V.; Izarova, Natalya V.; Nkala, Fiona M.; Kortz, Ulrich; Kompankov, Nikolay B.; Moroz, Nikolay K.; Sokolov, Maxim N.
Abstract Compounds (III) and (V) are characterized by single crystal XRD, 77Se NMR, FTIR, and Raman spectroscopy.